Investigating the properties of a galaxy group at z = 0.6. Issue Volume 15:Issue S359(2020) (March 2019) - Okido, Daniela Hiromi; Furlanetto, Cristina; Trevisan, Marina; Tergolina, Mônica
Abstract: Galaxy groups offer an important perspective on how the large-scale structure of the Universe has formed and evolved, being great laboratories to study the impact of the environment on the evolution of galaxies. We aim to investigate the properties of a galaxy group that is gravitationally lensing HELMS18, a submillimeter galaxy at z = 2.39. We obtained multi-object spectroscopy data using Gemini-GMOS to investigate the stellar kinematics of the central galaxies, determine its members and obtain the mass, radius and the numerical density profile of this group. Our final goal is to build a complete description of this galaxy group. In this work we present an analysis of its two central galaxies: one is an active galaxy with z = 0.59852 ± 0.00007, while the other is a passive galaxy with z = 0.6027 ± 0.0002. Furthermore, the difference between the redshifts obtained using emission and absorption lines indicates an outflow of gas with velocity v = 278.0 ± 34.3 km/s relative to the galaxy.